2013
DOI: 10.1177/0961203313486951
|View full text |Cite
|
Sign up to set email alerts
|

Catatonia in systemic lupus erythematosus: a case report and review of literature

Abstract: Although, neuropsychiatric morbidity is quite high in patients with systemic lupus erythematosus (SLE), catatonia has been rarely reported. We report a case of a 22-year-old female who presented with catatonic symptoms at the time of relapse of SLE and have discussed the presentation in the context of existing literature with regard to phenomenology of catatonia, psychiatric co-morbidity and treatment of catatonia in patients with SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…Psychosis overall is uncommon in SLE and occurs in ,10% of patients with SLE. 5 In a recent review of the literature, Grover et al 6 identified 22 case reports of patients with SLE who developed catatonia, including patients whose initial presenting symptom of SLE was catatonia. Psychosis at the onset of SLE is associated with disease activity, and is associated more with positive antiphospholipid and ribosomal P antibodies than cutaneous or renal manifestations of SLE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Psychosis overall is uncommon in SLE and occurs in ,10% of patients with SLE. 5 In a recent review of the literature, Grover et al 6 identified 22 case reports of patients with SLE who developed catatonia, including patients whose initial presenting symptom of SLE was catatonia. Psychosis at the onset of SLE is associated with disease activity, and is associated more with positive antiphospholipid and ribosomal P antibodies than cutaneous or renal manifestations of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…14 Patients with SLE who develop psychosis usually do so in the first year of their SLE diagnosis and may present with paranoid delusions or audiovisual hallucinations, causing significant distress and social impairment. [6][7][8][9] To our knowledge, there are no controlled trails comparing treatment modalities of catatonia in patients with SLE. 14,15 It is important to identify and treat patients with SLE who develop psychosis, because these patients are at increased risk of developing other central nervous manifestations of SLE, such as strokes and seizures, and psychotic symptoms typically remit with treatment of the underlying SLE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent review,[6] authors presented the data of catatonia and SLE and concluded that there are only 22 cases of catatonia reported in literature to be associated with SLE and their case being the 23 rd . Of these 23 cases of catatonia in SLE, only eight cases[789101112131415] have been reported in patients younger than 18 years of age with youngest patient being aged 13 years.…”
mentioning
confidence: 99%